Student Attitudes Toward the Implementation of Scoring Rubric in Speaking Class - Sri Fatmaning Hartatik; Hernina Dewi Lestari; Maya Rizki Amalyasari; Jasuli (ITScience (Information Technology and Science), 2024)
The teaching of speaking has been challenging for English as a Foreign Language (EFL) learners, especially at higher education levels. This can be affected by internal factors like student interest and motivation and external factors like learners' first influence. One alternative that teachers can use to help students perform better in speaking class is a scoring rubric. This descriptive qualitative study was designed to elaborate and describe students' attitudes to using scoring rubrics in speaking performance classes. This study involved 25 students attending classes at a higher education level. To gain data from those twenty-five students, an observation checklist was used to detect students' behaviour and performance. An interview guide was used to determine student thoughts on the distributed scoring rubric. The observation checklist indicated that the students looked more confident in their speaking performance. Besides, their speaking performance was more organized. The interview confirmed these findings, resulting in students feeling more confident in presenting their project as the scoring rubric, which was distributed in advance, gave them hints on what to do. Also, the presented points for each criterion motivate them to fulfil the requirements to achieve their intended score. The study's findings show that using a scoring rubric in teaching speaking positively impacted students' performance attitudes. Consequently, the distribution of scoring rubrics as a tool to stimulate students' speaking is extensively advised.